Marcha em crianças e adolescentes com dor musculoesquelética idiopática - Costa, Maria da Conceicao Rodrigues Goncalves da [UNIFESP] (2017)
Objective: To study the gait of children and adolescents with idiopathic musculoskeletal pain (IMSP) through dynamic baropodometry. Method: We included 32 patients with IMSP followed at a specialized pain clinic and 32 controls with no history of musculoskeletal pain, matched by age, sex, social class and Body Mass Index (BMI). All participants have been evaluated for the intensity of musculoskeletal pain through a Visual Analogue Scale (VAS), with 0 (zero) = no pain and 10 (ten) =, much pain and have undergone gait evaluation through dynamic baropodometry (FootWalk Pro, AMcube®, Gargas, France). Results: The mean age of the IMSP group was 13.6 years (SD = 2.1; variation 9.8–16.9) and the mean age of the control group was 13.5 years (SD = 2.0; variation 9.6–16.5). The mean pain scale for the patients was 5.4. Regarding gait, we observed that the mean right foot velocity of the IMSP group was significantly lower than that of the control group (p = 0.034), the step time of the IMSP group was significantly higher than that of the control group (p = 0.003) and the cadence of the IMSP group was significantly lower than that of the control group (p = 0.001). Conclusion: Children and adolescents with IMSP present gait alterations when submitted to dynamic baropodometry.